The genetic history of Australia, Oceania, and Southeast Asia 1 - Stoneking, Mark (Henry Stewart Talks, 2015)
Types of genetic markers, Oceania: divisions past and present, How many dispersals of modern humans from Africa, Genetic evidence: links with India